Does hospital readmission following colorectal cancer resection and enhanced recovery after surgery affect long term survival?. (2nd August 2017) - Curtis, N. J.; Noble, E.; Salib, E.; Hipkiss, R.; Meachim, E.; Dalton, R.; Allison, A.; Ockrim, J.; Francis, N. K.
Abstract: Aim: Hospital readmission is undesirable for patients and care providers as this can affect short‐term recovery and carries financial consequences. It is unknown if readmission has long‐term implications. We aimed to investigate the impact of 30‐day readmission on long‐term overall survival (OS) following colorectal cancer resection within enhanced recovery after surgery (ERAS) care and explore the reasons for and the severity and details of readmission episodes. Method: A dedicated, prospectively populated database was reviewed. All patients were managed within an established ERAS programme. Five‐year OS was calculated using the Kaplan–Meier method. The number, reason for and severity of 30‐day readmissions were classified according to the Clavien–Dindo (CD) system, along with total (initial and readmission) length of stay (LoS). Multivariate analysis was used to identify factors predicting readmission. Results: A total of 1023 consecutive patients underwent colorectal cancer resection between 2002 and 2015. Of these, 166 (16%) were readmitted. Readmission alone did not have a significant impact on 5‐year OS (59% vs 70%, P  =   0.092), but OS was worse in patients with longer total LoS (20 vs 14 days, P  =   0.04). Of the readmissions, 121 (73%) were minor (CD I–II) and 27 (16%) required an intervention of which 16 (10%) were returned to theatre. Gut dysfunction 32 (19%) and wound complications 23 (14%) were the most frequent reasons for readmission. Prolonged initial LoS, rectal cancer and younger age predicted for hospital readmission. Conclusion: Readmission does not have a significant impact on 5‐year OS. A broad range of conditions led to readmission, with the majority representing minor complications.